Odpowiedzi

2010-01-09T14:19:20+01:00
12(5a-2)-8(6a-7b)+3(3a-12b)= 60a - 24 -48a + 56b +9a - 36b= 21a + 20b -24

5(4a-b)-9(b-2a)+7(3a-7b)= 20a -5b -9b +18a +21a - 49b =59a -63b

2a(x+5y)+3x(a-5y)=2ax + 10 ay +3ax - 15xy = 5ax +10 ay -15xy

-4b(2a-8y)+3y(b-7a)=-8ab +32by +3by - 21ay = 8ab + 35by - 21ay
2010-01-09T14:23:31+01:00
A ) 60a - 24 - 48a + 56b + 9a - 36b = 60a - 48a + 9a + 56b - 36b - 24= =21a + 20b - 24

b) 20a - 5b - 9b + 18a + 21a - 49b = 20a + 18a + 21a - 5b - 9b - 49b =
= 59a - 63b

c)2ax + 10ay + 3ax - 15ay = 5ax - 5ay

d) -8ay + 32by + 3by - 21ay = -29ay + 35 by